Numerical Investigation on Effect of Food Particle Mass on Spout Elevation of a Gas–Particle Spout Fluidized Bed in a Microwave–Vacuum Dryer - Jin, G.; Zhang, M.; Fang, Zhongxiang; Cui, Z.; Song, C. (Taylor and Francis Inc., 2015)
The effect of food particle mass on the instantaneous fluid dynamic characteristics of a gas–particle spout fluidized bed in a pulsed spouted microwave–vacuum drying (PSMVD) system was investigated by a numerical method. The spout fluidization process in a pseudo-2D spout fluidized bed was simulated by computational fluid dynamics (CFD) using the inviscid two-fluid theory method (TFM) based on the kinetic theory of granular flow. The effect of particle mass on the particle flow pattern, jet penetration depth, and pressure drop was evaluated. Under a specific particle mass, the spout velocity was an important factor controlling particle status in the spout fluidized bed and a critical velocity was identified for effective transition of the flow pattern. With an increase in particle mass, the spout velocity tended to increase to obtain the expected gas–particle flow pattern and the correlation between the particle mass and particle flow pattern was revealed. This research on the fluid dynamic characteristics of a gas–particle spout fluidized bed could be used to improve the uniformity of particle mixing and microwave heating.